Provisional Measures in the Case Concerning Application of the International Convention on the Elimination of All Forms of Racial Discrimination (Georgia v. Russian Federation) - Tobias Thienel (Göttingen Journal of International Law)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} p.MsoFootnoteText, li.MsoFootnoteText, div.MsoFootnoteText {mso-style-noshow:yes; margin-top:0cm; margin-right:0cm; margin-bottom:0cm; margin-left:21.25pt; margin-bottom:.0001pt; text-align:justify; text-indent:-21.25pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} span.MsoFootnoteReference {mso-style-noshow:yes; vertical-align:super;} p.ArticleText, li.ArticleText, div.ArticleText {mso-style-name:"Article Text"; mso-style-update:auto; margin:0cm; margin-bottom:.0001pt; text-align:justify; text-indent:1.0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:KO;} span.apple-style-span {mso-style-name:apple-style-span; font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} /* Page Definitions */ @page {mso-footnote-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") fs; mso-footnote-continuation-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") fcs; mso-endnote-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") es; mso-endnote-continuation-separator:url("file:///C:/DOKUME~1/mlippold/LOKALE~1/Temp/msohtml1/01/clip_header.htm") ecs;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 70.85pt 2.0cm 70.85pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> On 15 October 2008, the International Court of Justice indicated provisional measures under Article 41 of its Statute in the Case concerning Application of the International Convention on the Elimination of All Forms of Racial Discrimination (Georgia v. Russia).<!--[if !supportFootnotes]-->[1]<!--[endif]--> By these measures, it instructed both Russia and Georgia to refrain from specified violations of the Convention,<!--[if !supportFootnotes]-->[2]<!--[endif]--> to do all in their power to prevent their public authorities from committing such violations, to facilitate humanitarian assistance, and to generally refrain from any action which might prejudice the rights under adjudication in the case. The Order of the Court was made by a vote of eight to seven, and gave rise to a Joint Dissenting Opinion by seven judges. Those judges expressed not only their dissent from the making of the Order, but also their disagreement with the majority’s finding of even prima facie jurisdiction.<!--[if !supportFootnotes]-->[3]<!--[endif]--> The case has already raised a few interesting issues relating to the Court’s jurisdiction to indicate provisional measures, and to the interpretation of CERD. These issues were all hotly contested not only between the parties, but also between the judges of the ICJ. This note will give a brief overview of the decision of the Court, and will comment on some outstanding features of the different opinions expressed. <!--[if !supportFootnotes]--> <!--[endif]--> <!--[if !supportFootnotes]-->[1]<!--[endif]--> Application of the International Convention on the Elimination of All Forms of Racial Discrimination (Georgia v. Russian Federation), Order of 15 October 2008 (Georgia v. Russia), available at http://www.icj-cij.org/docket/files/140/14801.pdf (last visited 10 December 2008). <!--[if !supportFootnotes]-->[2]<!--[endif]--> International Convention on the Elimination of All Forms of Racial Discrimination, 21 December 1965, 660 U.N.T.S. 195 (hereinafter CERD). On the measures indicated by the Court, see further Section D below. <!--[if !supportFootnotes]-->[3]<!--[endif]--> Georgia v. Russia (see, supra, note 1), Joint Dissenting Opinion of Vice-President Al-Khasawneh and Judges Ranjeva, Shi, Koroma, Tomka, Bennouna and Skotnikov, esp. para. 23 (Joint Dissenting Opinion) available at http://www.icj-cij.org/docket/ files/140/14805.pdf (last visited 10 December 2008).